The Role of Transformational Leadership and HR Governance in Shaping Enterprise Risk Management and Corporate Performance - Hamzah, Amir; Dini, Maya; Amaliah, Ima; Nurhayati, Nunung (Journal of Social Science and Business Studies, 2026)
This study aims to examine the relationship between Transformational Leadership, Human Resource (HR) Governance, and the implementation of Enterprise Risk Management (ERM), as well as their contribution to firm performance. Using a quantitative approach and multiple linear regression models that satisfy classical assumptions, the study finds that Transformational Leadership and HR Governance do not have a significant effect on ERM implementation. This indicates that in large organizations such as state-owned enterprises, risk management systems are more influenced by regulations, oversight mechanisms, and institutional structures than by individual initiatives. Furthermore, Transformational Leadership significantly improves firm performance when tested without mediating variables; however, its effect becomes insignificant when ERM is included, highlighting the dominant role of ERM in determining performance. HR Governance also shows no significant effect on performance, suggesting the need to shift the HR function from administrative to strategic roles. On the other hand, ERM has a significant and independent effect on firm performance without mediating the influence of leadership or HR Governance. These findings imply that strengthening ERM implementation can sustainably enhance firm performance, while the development of leadership quality and HR strategies remains essential to support the organization’s long-term objectives.